Potentials of technical tours for special interest tourists in Kuala Lumpur - Zakariya, Khalilah; Che Haron, Roziha; Yusof, Zeenat Begam; Ibrahim, Illyani (e-International Publishing House, Ltd., UK, 2020)
Within the last ten years, there has been growing attention to Special Interest Tourism (SIT). This article examined the sites in Kuala Lumpur that have potentials to attract built environment professionals and design enthusiasts. This study uses secondary data from technical tours, tour packages and attractions offered by various agencies. The data gathered are mapped, tabulated and analysed. The findings revealed that Kuala Lumpur has potentials to promote 58 sites in the city for Special Interest Tourism. These results may help professional bodies, destination managers, tourism operators and site/building owners to enhance and position their sites as attractions for SIT.